The global disinflation puzzle: A selective review of the theory and evidence in an historical context - Emilio Ocampo (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2020)
In the last three decades average inflation rates have declined around the world. Since 1995 the number of countries with inflation rates below 10% a year increased from 98 (54% of the total) to an average of 178 in 2015-2019 (90% of the total). In the aftermath of the 2008 Global Financial Crisis (GFC), inflation in the US has averaged 1.8% a year despite an unprecedented monetary expansion, and more recently, a drop in the unemployment rate to historical lows. In the last decades, two of modern macroeconomic theory's most important relationships appear to have broken down: the Quantity Theory of Money (QTM) and the Phillips Curve (PC). This paper i) presents evidence that confirms the global disinflationary trend of the last three decades, ii) identifies previous historical episodes during which the QTM appeared to break down in the US and the UK and the theoretical reassessment that it provoked, iii) examines experts' reaction to the apparent current breakdown of the QTM and the PC and the alternative paradigms that have emerged, and iv) reviews the alternative hypotheses that have been proposed to explain global disinflation, focusing particularly on the effects of technological innovation and globalization.
Keywords: 330; Inflationsbekämpfung; Internationaler Finanzmarkt; Geldtheorie